Evaluation of Intraperitoneal and Incisional Bupivacaine or Levobupivacaine for Postoperative Analgesia in Ovariohysterectomized Dogs - Korkmaz, Musa; Yilmaz, Oktay; Kadir Saritas, Zulfukar; Demirkan, Ibrahim; Jaroszewski, Jerzy (Acta Scientiae Veterinariae, 2019)
Background: Ovariohysterectomy (OHE) is the most commonly performed elective surgical procedure in companion animals. OHE offers benefits of control of population and decreased risk of potentially life-threatening diseases such as mammarian tumours and pyometra. Traditional OHE intervention causes inflammation and pain due to trauma during organ manipulation. The purpose of this study was to compare the effect of intraperitoneal and incisional administration of bupivacaine (BP) or levobupivacaine (LP) on postoperative analgesia in dogs undergoing the OHE procedure. Materials, Methods & Results: A total of 24 mix-breed bitches aged between 1 - 3 years and weighed 19 - 20 kg were used in this study. The animals were divided into three groups as control (n = 8), BP (n = 8) and LP group (n = 8). The animals were kept under surveillance at the hospitalisation unit of the animal hospital for one day before the elective OHE. The dogs were fasted for 12 h before the surgery, with adlib water consumption. Atropine sulphate 0.045 mg/kg was administered subcutaneously approximately 30 min before general anaesthesia. Midazolam (0.3 mg/kg) was intravenously injected into all dogs for pre-anaesthetic medication. After sedation, anaesthesia was induced with propofol (4 mg/kg, IV) and then the dogs were orotracheally intubated using cuffed endotracheal tubes. General anaesthesia was maintained by administration of 2% isoflurane. The ventral abdomen was prepared aseptically for OHE following the general anaesthesia. All animals were operated on by the same surgeon. During surgery, sprayed bupivacaine 0.5% (4.4 mg/kg) with an equal volume of saline in BP group, levobupivacaine 0.5% (4.4 mg/kg) with an equal volume of saline in LP were then applied over the ovaries, uterine broad ligaments and cervix uteri. After removal of the uterine body, either LP or BP was sprayed to left and right, or cranial and caudal parts of the abdominal cavity. Finally, the incision line was sprayed before closing the skin. The control group received only sprayed saline. The pain evaluation was carried out with modified Melbourne pain scoring scale. To determine cortisol concentrations, blood samples were taken before anaesthesia induction (baseline) and postoperative 0, 0.5, 1, 2, 4, 6, 12 and 24 h. Postoperative pain scores were higher in the control group than BP and LP groups following surgery at 30 min, 1st, 4th, and 6th h. In all groups, cortisol levels increased postoperatively, whereas they decreased more rapidly in BP and LP groups. There was a steady increase at postoperative 0 min, 30 min, 1st, 2nd, 4th and 6th h in the control group and at postoperative 0 min, 30 min and 1 h in BP and LP groups (P < 0.05). Discussion: Intraperitoneal and incisional bupivacaine shows significantly superior postoperative pain management benefits after the closure of skin, compared to untreated dogs and it is also superior to lidocaine treatment at 0.5 h following the visual analogy pain assessment system. In the present study, the observation of lower pain scores in BP group at 0.5, 1, 4 and 6 h as compared to the control group was similar to findings of other studies. LP group also showed decreased pain scores at above-mentioned h without any significant difference. However, only in LP group, pain scores at 24 h were lower than postoperative pain scores. In conclusion, it is suggested that sprayed intraperitoneal and incisional BP and LP are very effective for preventing postoperative pain ovariohysterectomized dogs.